Implications of past and present equivocations in reproducing or challenging epistemic violence in encounters with difference - Manresa Axisa, Antonia (Language and Intercultural Communication, 2025)
Based on an ethnographic research study, in an Ecuadorian Amazonian Kichwa territory, I use the notion of ‘translation as controlled equivocation’ as an analytical tool to explore the making sense of difference. Occurring in the same territory, I analyse these encounters with difference, read in relation to a classroom dialogue between teacher and students, with that of a historical encounter with the ‘other’ in a Dominican missionary’s diary of 1887/1888. I propose that exploring the processes of equivocation centring differing subjective positions and situated dialogues, provides a reflective tool against reproducing epistemic violence whilst making space to recognize difference. Basado en una investigación etnográfica, en un territorio Kichwa Amazónico Ecuatoriano, uso como concepto de análisis la ‘traducción como equivalencia controlada’ para entender la diferencia. Ocurridos en el mismo territorio, analizo dos encuentros con lo diferente, desde la lectura de un dialogo en clase entre estudiantes y docente, y el encuentro histórico con el ‘otro’ del diario de un misionero Dominico (1887/1888). Centrándose en las diferentes posiciones subjetivas y los diálogos en los que se llevan acabo, argumento que la exploración de equivalencias sirve de mecanismo de reflexión enfrentado la reproducción de violencia epistémica en el reconocimiento de la diferencia.